Utilization of Chatbot in Transaction Business Process - Hidayat, M I; Luckyardi, S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out how the use of chatbots is a factor in product sales growth. For example, the use of chatbots as a substitute for customer service. This research method was collecting data based on several survey results from various reliable sources. The results of this study are expected to provide enlightenment for business people about the importance of making innovations and utilizing this chatbot in selling their products. By using this chatbot system, business owners no longer need to use the services of third parties or recruit new employees, so as not to incur new expenses. The use of this system may only be complementary, but the impact can be very large because with chatbot customer service does not need to be on standby for 24 hours, with chatbot customers can be served anytime and anywhere.